SULFUR PARTITIONING BETWEEN APATITE AND MELT AND EFFECT OF SULFUR ON APATITE SOLUBILITY AT OXIDIZING CONDITIONS - Parat F.; Holtz F. (My University, 2004)
The effect of sulfur on phosphorus solubility in rhyolitic melt and the sulfur distribution between apatite, anhydrite, melt and fluid have been determined at 200MPa and 800–1,100C via apatite crystallization and dissolution experiments. The presence of a small amount of sulfur in the system (0.5wt.% S) under oxidizing conditions increases the solubility of phosphorus in the melt, probably due to changing calcium activity in the melt as a result of the formation of Ca-S complexing cations. Apatite solubility geothermometers tend to overestimate temperature in Ca-poor, S-bearing system at oxidizing conditions. In crystallization experiments, the sulfur content in apatite decreases with decreasing temperature and also with decreasing sulfur content of the melt. The sulfur partition coefficient between apatite and rhyolitic melt increases with decreasing temperature (KdSapatite/melt=4.5–14.2at T=1,100–900C) under sulfur-undersaturated conditions (no anhydrite). The sulfur partition coefficient is lower in anhydrite-saturated melt (~8at 800C) than in anhydrite-undersaturated melt, suggesting that KdSapatite/melt depends not only on the temperature but also on the sulfur content of the melt. These first results indicate that the sulfur content in apatite can be used to track the evolution of sulfur content in a magmatic system at oxidizing conditions.